2019
DOI: 10.1093/conphys/coz061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of traffic noise exposure on corticosterone, glutathione and tonic immobility in chicks of a precocial bird

Abstract: Repeated exposure to traffic noise may be perceived as a succession of stressors, and therefore, noisy urban environments could lead to a state of chronic stress. In developing animals, glucocorticoids can have organizational effects on the hypothalamic–pituitary–adrenal axis in addition to the classic activation effects, so evaluating the effect of traffic noise during development is urgently needed. To our knowledge, to date six studies have investigated the effects of traffic noise on baseline corticosteron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 80 publications
1
12
0
Order By: Relevance
“…Regarding noise pollution specifically, results are also contrasting. Studies using nestling birds (incapable of avoiding noise sources) as focal individuals have found that experimental exposure to traffic noise can lead to both increases and decreases of baseline CORT levels (Injaian et al 2018b(Injaian et al , 2019Crino et al 2013;Flores et al 2019) and no effects at all (Meillère et al 2015a, b;Angelier et al 2016). Most correlational studies reported no influence of noise exposure on CORT (Crino et al 2011;Casasole et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding noise pollution specifically, results are also contrasting. Studies using nestling birds (incapable of avoiding noise sources) as focal individuals have found that experimental exposure to traffic noise can lead to both increases and decreases of baseline CORT levels (Injaian et al 2018b(Injaian et al , 2019Crino et al 2013;Flores et al 2019) and no effects at all (Meillère et al 2015a, b;Angelier et al 2016). Most correlational studies reported no influence of noise exposure on CORT (Crino et al 2011;Casasole et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory studies using rats showed that noise increased oxidative damage and free radical concentration and triggered antioxidant enzymatic responses (Demirel et al 2009;Said and El-Gohary 2016). In nestling birds, experimental studies have reported increases in oxidative stress levels (Injaian et al 2018a) and upregulations of different components of the antioxidant machinery (Flores et al 2019). Interestingly, recent studies have reported that nestlings in noisy environments possess shorter telomeres (Meillère et al 2015a, b;Grunst et al 2020), a pattern that may be proximally linked to oxidative stress and glucocorticoids (Haussmann et al 2011, Monaghan 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in baseline corticosterone levels have also been noted, although the direction of the effect has been variable. For example, in some cases, CORT has been found to increase ( Injaian et al , 2019 ), decrease ( Kleist et al , 2018 ) and not change ( Flores et al , 2019 ) in response to noise.…”
Section: Introductionmentioning
confidence: 99%
“…In response to stress events, the hypothalamic–pituitary–adrenal axis is activated and CORT is released ( Kleist et al , 2018 ). Repeated stress events can cause a chronic stress response, ultimately changing baseline corticosterone levels, a measure of long-term fitness ( Bonier et al , 2011 ; Flores et al , 2019 ). However, the amount and direction of change of baseline CORT is highly variable depending on individuals, species and circumstances ( Bonier et al , 2011 ; Curry et al , 2018 ; Flores et al , 2019 ; Injaian et al ., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation